Introducing Basic Occupational Safety and Health to Sixth-Grade Students at SD Negeri 011 Balikpapan - Angel Lian Iskandar; Fitri Yanti; Najwa Kamiilah Yusuf; Salwa Nafisa Putri; Gilbert Alvons Wala; Naufalditya Alainal Arzaaqa; Retnowaty Retnowaty; Ari Musdolifah; Nurliani Maulida (EUNOIA, 2026)
An Occupational Safety and Health (OSH) awareness program for sixth-grade students at SD Negeri 011 Balikpapan Kota was conducted as an effort to instill a culture of safety from an early age. The program was carried out through presentations using presentation media, direct interaction, question and answer sessions, quizzes, educational games, and the distribution of snacks to all students. A total of 30 students participated in this activity, with two students asking questions and around 8-10 students actively participating in answering quizzes. The results of the activity showed that interactive delivery methods were able to improve students' understanding of basic OSH concepts, such as types of hazards, safety rules at school, the use of simple personal protective equipment, and first aid measures. This activity also increased students' enthusiasm for learning about safety. These findings indicate that OSH socialization with an interesting and age-appropriate approach can be an effective strategy in building safety awareness in elementary school environments.